Stimulation Of Early Children’s Ability To Hear By Story Activity - Nopia Yuliandari; Melta Santri Hardila; Delfi Eliza (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2021)
To be able to support children's general cognitive ability and aspects of effective communication, enhancement of listening abilities in early childhood is very important. The researcher explains items related to early childhood language in this case. This research aimed to see how to stimulate early childhood listening skills through storytelling activities. Literature analysis research using the outcomes of reviewing papers, books, and similar relevant sources is the type of research used. The outcome of this research is that storytelling can impact early childhood listening capacity and can attend the focus of children onlistening to what other people say through storytelling activities.